2021
DOI: 10.3390/v13122528
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Outcome of Coinfections with SARS-CoV-2 and Rhinovirus

Abstract: Background: We aimed to compare the clinical severity in patients who were coinfected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and rhinovirus or monoinfected with a single one of these viruses. Methods: The study period ranged from 1 March 2020 to 28 February 2021 (one year). SARS-CoV-2 and other respiratory viruses were identified by real-time reverse-transcription-PCR as part of the routine work at Marseille University hospitals. Bacterial and fungal infections were detected by stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 20 publications
5
35
1
Order By: Relevance
“…4 , 5 , 6 Also, in a retrospective study, the most common coinfected microorganism was found to be Mycoplasma pneumoniae (25%), followed by virus (7%) and bacteria (5%). 7 Similar to previous literature, 2 , 3 , 4 , 5 , 6 the authors demonstrated four times human rhinovirus (A and B), thrice both human coronavirus (229E and OC43) and mastadenovirus A, and once Influenza A virus. 1 …”
supporting
confidence: 86%
See 1 more Smart Citation
“…4 , 5 , 6 Also, in a retrospective study, the most common coinfected microorganism was found to be Mycoplasma pneumoniae (25%), followed by virus (7%) and bacteria (5%). 7 Similar to previous literature, 2 , 3 , 4 , 5 , 6 the authors demonstrated four times human rhinovirus (A and B), thrice both human coronavirus (229E and OC43) and mastadenovirus A, and once Influenza A virus. 1 …”
supporting
confidence: 86%
“…We have read the article titled to ‘Coinfection with severe acute respiratory syndrome coronavirus‐2 and other respiratory viruses at a tertiary hospital in Korea’ by Lee et al 1 In this manuscript, we agree with the authors that SARS‐CoV‐2 coinfections with other respiratory tract infection (RTI) viruses recently have begun to draw attention. 2 , 3 In this study, the authors explored specific RTI viruses and their possible relations with SARS‐CoV‐2.…”
mentioning
confidence: 99%
“…Recently, 7 coronaviruses have been reported to be able to integrate se-quences putatively from insects [36]. Such natural mosaicisms in these viruses make it possible to understand the emergence of RNA viruses and should lead to a strengthening of genomic surveillance in patients presenting with coinfections by several RNA viruses, as is observed in patients infected with several respiratory viruses including SARS-CoV-2, endemic human coronaviruses, influenza viruses, or rhinoviruses [37]. Such infectious episodes could perhaps lead to the creation of new emerging viruses, as has been for instance reported for enteroviruses of humans and great apes [38].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of RSV, this occurred out of its normal seasonal pattern ( 2 , 3 ). As SARS-CoV-2 continues to circulate in human populations worldwide, there are overlapping incidences of COVID-19 and other respiratory viral infections ( 4 ). Circulation of rhinovirus (RV) was less affected than influenza viruses and RSV by public health measures intended to slow SARS-CoV-2 transmission, and RV has been frequently detected as a co-pathogen in COVID-19 patients ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…As SARS-CoV-2 continues to circulate in human populations worldwide, there are overlapping incidences of COVID-19 and other respiratory viral infections ( 4 ). Circulation of rhinovirus (RV) was less affected than influenza viruses and RSV by public health measures intended to slow SARS-CoV-2 transmission, and RV has been frequently detected as a co-pathogen in COVID-19 patients ( 4 , 5 ). Multiple studies have proposed that RV infections mediate viral interference with heterologous respiratory viruses, including influenza viruses and SARS-CoV-2 ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%